Effect of early calf-hood nutrition on the transcriptomic profile of subcutaneous adipose tissue in Holstein-Friesian bulls - Anne-Marie English; Sineád M. Waters; Paul Cormican; Colin J. Byrne; Seán Fair; David A. Kenny (BMC Genomics, 2018)
Abstract Background Adipose tissue is a major endocrine organ and is thought to play a central role in the metabolic control of reproductive function in cattle. Plane of nutrition during early life has been shown to influence the timing of puberty in both male and female cattle, though the exact biological mechanisms involved are currently unknown. The aim of this study was to investigate the effect of early calf-hood nutrition on the transcriptomic profile of subcutaneous adipose tissue in Holstein-Friesian bulls to identify possible downstream effects on reproductive physiology. Results Holstein-Friesian bull calves with a mean (±S.D.) age and bodyweight of 19 (±8.2) days and 47.5 (±5.3) kg, respectively, were assigned to either a high (n = 10) or low (n = 10) plane of nutrition. Calves were fed in order to achieve an overall growth rate of 1.08 and 0.57 kg/day for the high and low plane of nutrition treatments, respectively. At 126 days of age, the bulls were euthanized, subcutaneous adipose tissue samples were harvested and RNAseq analysis was performed. There were 674 genes differentially expressed in adipose tissue of calves on the low compared with the high plane of nutrition (P < 0.05; FDR < 0.05; fold change > 2.0). High plane of nutrition positively altered the expression of genes across an array of putative biological processes but the most dominant cellular processes affected were cellular energy production and branched chain amino acid degradation. A high plane of nutrition caused upregulation of genes such as leptin (LEP) and adiponectin (ADIPOQ), which are known to directly affect reproductive function. Conclusions These results provide an insight into the effect of augmenting the plane of nutrition of Holstein-Friesian bull calves in the prepubertal period on the transcriptome of adipose tissue.